Applying ELMS Technology Based Teaching Strategy to Improve Writing Competence for EFL Remedial Students across Different Motivation Level - ., Sujito; Kurniasih, Nuning; Mahir Muttaqin, Wildan; Novita Sari, Ifit; Paulus Saleky, Andre; Tuasikal, Patma; Talakua, Yani; Mendelson Laka, Beatus; Niwele, Amelia; Aziz, Firman (International Journal of Engineering and Technology, 2018)
Technology provides an alternative to improve learning outcomes in new ways. ELMS (Edmodo Learning Management System) technology based teaching is expected to provide solutions in teaching English in Indonesia, especially for teaching writing. This research is to determine how application technology can improve the writing ability of remedial students who are low motivated. This study was aimed to see the difference of the remedial students’ writing competence before and after taught using ELMS teaching technology by considering learnersâ€™ motivation level. This study used experimental design using factorial design 2x2. Two classes of remedial learners consisted of 30 students for each group was assigned into 2 smaller groups to match with their motivation falling into two classifications: high and low motivation. The two groups were given treatment for about 7 meetings. The study revealed three findings. First, learning achievement of the subjects after given subtext application teaching technology was higher than the subjects given conventional non technology media writing. Second, the learning achievement of the subjects having high motivation was higher than the learning achievement of the subject with low motivation. Third, there was significant interaction between the use of application teaching technology with the subjects’ motivation level towards writing achievement improvement of the first year remedial EFL students. Â Â